Numerical analysis of perforated built-up open cold-formed steel beam - Noradila, Mohd Alias (2018)
The linear analysis and linear buckling analysis of built-up open sections of cold-formed steel subjected to bending was investigated. A total of 18 beams having different shapes and size of web opening were tested under four point bending by using Finite Element Analysis. The built-up sections were assembled by self-tapping screws from two plain channels. The objectives was to study the effect of perforations having different shapes and sizes together to determine the maximum buckling load that can be carried by eigenvalue bucking analysis and to identify the mode of failure of the sections under elastic bending stress. Finite element model was developed using LUSAS 14.0 software to analyse the specimens having two different shapes of perforation which are circular and square shapes with a different number of opening and sizes. Different length of beam sections used was; short 1000 mm (1), medium 1500 mm (2) and slender 2000 mm (3). Pinned and Roller ended support was assigned to validate the Finite Element Analysis. The localized failure due to the size and number of opening in the web plates of the builtup CFS beam is observed. The results shown the maximum buckling load and the mode of failure of cold-formed steel beam vary with the perforations position.